ANALISIS PENYELESAIAN MASALAH MATEMATIKA PADA PEMBELAJARAN YANG MENGGUNAKAN PENDEKATAN SAINTIFIK DI KELAS VII - Arief Rahman Hakim (MEJ (Mathematics Education Journal), 2017)
This research aims to knowing the students when solving mathematical problemsin learning used scientific approach in class VII C SMPN 11 Malang. This type of research is descriptive qualitative approach. This research was conducted in SMPN 11 Malang on 7, 11, and August 14, 2015. Object of this study is the activity of students in solving mathematical problems. The subjects were students of class VII C SMPN 11 Malang. Methods of data collection in this study of student observation sheet, interview, and documentation.The results showed that : Activity of students when solving mathematical problems in learning used scientific approach has been implemented properly in accordance syntax that has been planned although the results are still not optimal. The results of observations at the first meeting showed that there were 36 students who observed the problem, three students were asked 27 students to reason, 23 students tried to solve it, two students presenting answers. The second meeting of the study there were 36 students observe the problem, two students asked 33 students to reason, 29 students tried, 4 students present.The third meeting there were 36 students observe, 4 students asked, 32 reasoning, 28 tries,and no students were present.